Primary Sclerosing Cholangitis and Inflammatory Bowel Disease - Escobar, Jessica Colin; Pereyra, Maria Navarez; Abbass, Mohammad Ali (The Surgical clinics of North America, 2025)
Primary sclerosing cholangitis (PSC) is a rare pathology seen in patients with inflammatory bowel disease (IBD), especially ulcerative colitis. PSC increases patients' morbidity and requires the attention of a multidisciplinary team as those patients require frequent colonoscopies and biopsies due to the elevated risk of malignancy, biliary screening and management of progressive disease that could leave patients in liver failure requiring liver transplant. Some consider this a separate form of IBD in addition to Crohn's and ulcerative colitis. These patients should be monitored closely and managed carefully due to implications of ongoing management on quality of life and survival.